Optimizing the Migratory Environment of Wildebeests in the Maasai Mara Reserve with a New Ecological Corridor and Customized Buffer Zone Model - Xinrui Fan; Kuok Ho Daniel Tang; Shoushuo Liu; Yang Liu; Charles Ken Smith (Earth)
Conflicts between wildlife and humans are a major ecological issue. During migration, wildlife, especially wildebeest, often encounter significant environmental pressures from human activities. However, relatively few studies have been conducted to provide a concise, quantitative description of wildebeest migration in the Maasai Mara National Reserve (MMNR). In this study, we identified changes in the location of the wildebeest population over time in the Maasai Mara National Reserve. We then used a K-means algorithm (R2 = 0.926) to fit coordinates representing the changes in the location of the wildebeests to enable a quantitative representation of their migration routes. Subsequently, we developed an environmental stress model to assess the changes in environmental stresses faced by wildebeests along their migration routes. We proposed a model of “migratory ecological corridors and customized buffer zones” and determined the response coefficient T_res. We used the response coefficients T_res = 0.06, 0.09, and 0.12 as the critical values to categorize the areas along the routes into weak, medium, and strong response regions. Then, we set the width of the buffer zones on both sides of the routes as 5 km, 7 km, and 9 km, respectively, and evaluated the buffer effect. This type of model achieved a good effect of reducing the environmental pressure by 54.06%. The “Migratory Ecological Corridor and Customized Buffer Zone” model demonstrated a high degree of economic feasibility while showing good practicality in mitigating the environmental conflicts between humans and migratory wildlife. The variability in the environmental pressures across the region indicates that the Nairobi and Nakuru districts may be undergoing a particular stage of urbanization that unleashes potential threats to the migration of wildebeests. Further research is essential to assess the feasibility of larger buffer zones.